Effects of Veratrum nigrum alkaloids on central catecholaminergic neurons of renal hypertensive rats - Li Hua; Gao Guang-You; Li Shu-Yuan; Zhao Wei-Jie; Guo Yong-Tian; Liang Zi-Jun (Acta Pharmacologica Sinica, 2016)
AIM: To study the central hypotensive mechanism of Veratrum nigrum L var ussurience Nakai alkaloids (VnA) in renal hypertensive rats(RHR). METHODS: The quantitative method of immunocytochemistry (ICC) was used to observe and detect the effect of VnA (30 micrograms.kg-1, i.v.) on activity of central catecholaminergic (CA) neurons of C1, C2, A1, and A5 areas in RHR. RESULTS: VnA increased the immunoreactivity (IR) of tyrosine 3-monooxygenase (TM)-immunopositive (IP) neurons of C1, C2, and A5 areas in RHR experimental group compared with RHR control group [positive units: (1.9 +/- 0.4), (1.18 +/- 0.23), (1.2 +/- 0.4) vs (0.15 +/- 0.22), (0.31 +/- 0.16), (0.69 +/- 0.20), respectively]; IR of TM-IP neurons of C1 and C2 areas in RHR control group was decreased compared with sham-operated group [positive units: (0.15 +/- 0.22), (0.31 +/- 0.16) vs (1.45 +/- 0.29), (1.36 +/- 0.25), respectively]. CONCLUSION: VnA increased the activity of central CA neurons in RHR to exert its hypotensive effect.